Peluang dan Tantangan Penerapan Prinsip Permanent Soverignity Over Natural Resources di Indonesia - Popi Tuhulele (SASI, 2020)
Principle of permanent sovereignty over natural resources (PSNR) in international law are regulated in UN General Assembly Resolution Number 1515 (XV) 15 December 1960, and Resolution Number 1803, 14 December 1962, which recognizes permanent sovereignty over natural resources. The fact is that Indonesia which is rich in natural resources is not fully sovereign of its natural resources. This is influenced by limited capital ownership and also limited human resources. Because permanent sovereignty over natural resources should be directly proportional to the welfare of the people of Indonesia. This paper uses normative research methods with a database in the form of library data, online surveys, and several related legal materials, then described descriptively, and interpreted comprehensively. In this context, the importance of management and management of natural resources by the state. Because it is closely related to the risks posed by the exploitation and exploration of natural resources on geological and political aspects. For this reason, it is very important for Indonesia to adopt principles in supporting the rule of law at regional, international and national levels and protect the sovereignty and interests of the country.